Biodegradable Magnesium Alloys Developed as Bone Repair Materials: A Review. (13th March 2018) - Liu, Chen; Ren, Zheng; Xu, Yongdong; Pang, Song; Zhao, Xinbing; Zhao, Ying
Abstract : Bone repair materials are rapidly becoming a hot topic in the field of biomedical materials due to being an important means of repairing human bony deficiencies and replacing hard tissue. Magnesium (Mg) alloys are potentially biocompatible, osteoconductive, and biodegradable metallic materials that can be used in bone repair due to their in situ degradation in the body, mechanical properties similar to those of bones, and ability to positively stimulate the formation of new bones. However, rapid degradation of these materials in physiological environments may lead to gas cavities, hemolysis, and osteolysis and thus, hinder their clinical orthopedic applications. This paper reviews recent work on the use of Mg alloy implants in bone repair. Research to date on alloy design, surface modification, and biological performance of Mg alloys is comprehensively summarized. Future challenges for and developments in biomedical Mg alloys for use in bone repair are also discussed.